Mechanistic insights into nanoparticle surface-bacterial membrane interactions in overcoming antibiotic resistance - Modi, Suraj Kumar; Gaur, Smriti; Sengupta, Mrittika; Singh, Manu Smriti (Frontiers in Microbiology, 2023)
Antimicrobial Resistance (AMR) raises a serious concern as it contributes to the global mortality by 5 million deaths per year. The overall impact pertaining to significant membrane changes, through broad spectrum drugs have rendered the bacteria resistant over the years. The economic expenditure due to increasing drug resistance poses a global burden on healthcare community and must be dealt with immediate effect. Nanoparticles (NP) have demonstrated inherent therapeutic potential or can serve as nanocarriers of antibiotics against multidrug resistant (MDR) pathogens. These carriers can mask the antibiotics and help evade the resistance mechanism of the bacteria. The targeted delivery can be fine-tuned through surface functionalization of Nanocarriers using aptamers, antibodies etc. This review covers various molecular mechanisms acquired by resistant bacteria towards membrane modification. Mechanistic insight on ‘NP surface-bacterial membrane’ interactions are crucial in deciding the role of NP as therapeutic. Finally, we highlight the potential accessible membrane targets for designing smart surface-functionalized nanocarriers which can act as bacteria-targeted robots over the existing clinically available antibiotics. As the bacterial strains around us continue to evolve into resistant versions, nanomedicine can offer promising and alternative tools in overcoming AMR.